Meningkatkan Hasil Belajar Matematika Melalui Pendekatan Pemecahan Masalah dengan Strategi Polya Pada Siswa Kelas XI IPA SMA Negeri 2 Kalukku - sudirman . (Celebes Education Review, 2020)
The study is a classroom action research which aims at describing (1) the improvement of Mathematics learning result through problem solving approach by Polya strategy of class XI IPA students at SMAN 2 Kalukku, (2) the improvement of Mathematics problem solving skill by Polya strategy. The subject is students of class XI IPA of SMAN 2 Kalukku, as many as 31 people consisted of 11 male and 20 female students. The technique used to analyze the data is qualitative and quantitative analyses. The qualitative data is used on students’ activities while the quantitative data is used on students’ learning achievement and students’ response. The results indicate that (1) the application of problem solving approach by Polya strategy can improve students’ learning achievement on Mathematics indicated by the descriptive analysis of the average score of students’ learning achievement 65.42 at cycle I to 75.06 at cycle II; (2) the application of problem solving approach by Polya strategy can improve students’ problem solving skill on Mathematics indicated by percentage descriptive analysis, which is problem comprehension stage 83.87% at cycle I to 90.32% at cycle II, problem solving planning stage 87.10% at cycle I to 96.77% at cycle II,